2006
DOI: 10.1080/11250000600679991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological analysis of Tunisian populations ofPorcellio variabilisLucas (Crustacea, Isopoda, Oniscidea)

Abstract: Specimens of Porcellio variabilis coming from Tunisian populations were genetically and morphologically examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…These differences were a response to environmental variables rather than being a species-specific trait [33]. In order to better understand the importance of these factors in affecting breeding patterns, it would be interesting to study other populations of P. variabilis, especially the Ain Drahem population which seemed to be the most morphologically and genetically distinct [34].…”
Section: Identification Life Span and Recruitment Of Cohortsmentioning
confidence: 99%
“…These differences were a response to environmental variables rather than being a species-specific trait [33]. In order to better understand the importance of these factors in affecting breeding patterns, it would be interesting to study other populations of P. variabilis, especially the Ain Drahem population which seemed to be the most morphologically and genetically distinct [34].…”
Section: Identification Life Span and Recruitment Of Cohortsmentioning
confidence: 99%
“…Some illustrations made with the method of the present paper, were already published in other articles about terrestrial isopods: figure 1 in Medini-Bouaziz et al (2006); figure 2 in Montesanto et al (2007); figures 2, 3 in Montesanto et al (2008); figures 1–5 in Montesanto et al (2011); figures 1, 2 in Messina et al (2011); figure 1 in Messina et al (2012); figures 6, 7, and 9 in Montesanto et al (2012); figure 1 in Lupetti et al (2013); figures 2, 3 in Montesanto et al (2013); figures 1–6 in Messina et al (2014). Some indications about drawing terrestrial isopods for taxomomic papers are reported in Figure 7, whereas magnifications show the differences of the brush size for different anatomical parts.…”
Section: Resultsmentioning
confidence: 93%
“…In this last mentioned country, some studies were performed on reproductive behaviour, systematics, and geographical distribution of species of Hemilepistus, Porcellio, Porcellionides, and Armadillidium (cf. Rezig & Nasri, 1992;Nasri et al, 1996;Medini & Charfi-Cheikhrouha, 1998Achouri & Charfi-Cheikhrouha, 2000, 2001a, b, 2002, 2005, 2006Medini et al, , 2006Achouri et al, 2003;Hamaied & Charfi-Cheikhrouha, 2007).…”
Section: Introductionmentioning
confidence: 99%